Curriculum: Construction and Critique - Ross, Alistair (Routledge, 2000)
Although curriculum is central to the schooling process, debates about it are rarely well informed. Over the past ten years there has been a dearth of books that have informed the debate by examining curriculum in a broader context, beyond the National Curriculum. Ross, in this refreshing re-examination of the area, opens up a more general debate on how the curriculum is shaped and the compromises made between different ideologies of the nature and purpose of education.